Mechanisms of Cell Adhesion Molecules in Endocrine-Related Cancers: A Concise Outlook - Ruan, Yongsheng; Chen, Libai; Xie, Danfeng; Luo, Tingting; Xu, Yiqi; Ye, Tao; Chen, Xiaona; Feng, Xiaoqin; Wu, Xuedong (Frontiers in Endocrinology, 2022)
Chemotherapy is a critical treatment for endocrine-related cancers; however, chemoresistance and disease recurrence remain a challenge. The interplay between cancer cells and the tumor microenvironment via cell adhesion molecules (CAMs) promotes drug resistance, known as cell adhesion-mediated drug resistance (CAM-DR). CAMs are cell surface molecules that facilitate cell-to-cell or cell-to-extracellular matrix binding. CAMs exert an adhesion effect and trigger intracellular signaling that regulates cancer cell stemness maintenance, survival, proliferation, metastasis, epithelial-mesenchymal transition, and drug resistance. To understand these mechanisms, this review focuses on the role of CD44, cadherins, selectins, and integrins in CAM-DR in endocrine-related cancers.